Tafsir Ilmiah Sebagai Implementasi Integrasi Ilmu: Kasus UIN Maulana Malik Ibrahim Malang - Wardani, Wardani (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2022)
Following the changing status of many State Islamic Institutes of Islamic Studies into State Islamic Universities in Indonesia, the integration of Islam and science as the fundamental epistemological basis should be done, and its implementation has been characterized by attempts to interpret the Qur`an in the light of scientific perspective (al-tafsīr al-‘ilmī, scientific interpretation). This article is aimed to analyze thoughts on methods of this interpretation in the State Islamic University of Maliki (Malang) from Ian Barbour’s classification of modes of religion-science integration into the natural theology, the theology of nature, and philosophy of proccess. This article concludes that this university develops the theology of nature in the sense that the Qur`an through its paradigm and spirit is regarded to contain verses that explain many aspects of science. The “Qur`anic paradigm” constitutes a world-view that, as percieved, unifies many schools of thought and approach. Meanwhile, the “Qur`anic spirit” is moral teaching of the Qur`an that can be functioned as psychological explanations and solutions of human’s conditions.